Patterns of Virtual Reality Use and Associated Symptoms: A Comparative Study of Civilian and Military Users - Frankl, Dániel (Honvédségi Szemle – Hungarian Defence Review, 2025)
Virtual Reality (VR) technologies have become integral to modern military training, offering substantial advancements in operational preparedness, decision-making, and mission effectiveness. NATO forces, including the United States, the United Kingdom, and increasingly Hungary, have embraced VR solutions to improve joint interoperability and enhance realism in training scenarios, resulting in notable gains in threat identification accuracy and overall personnel readiness. However, the successful deployment of VR in military contexts necessitates an in-depth understanding of physiological and neurological considerations, such as cybersickness, cognitive overload, visual fatigue, and ergonomic strain, each of which can significantly impact soldiers’ cognitive performance and physical comfort. Empirical research conducted among military and civilian VR users reveals that military-trained individuals exhibit distinct psychological resilience, improved stress management, and heightened neurological adaptability compared to civilians. These measurable differences reinforce VR’s value as a strategic training asset, particularly when supported by ergonomically optimized equipment and adaptive, neurophysiologically informed training protocols. Consequently, continued investment in human-centered VR development is essential to fully leverage the operational advantages offered by immersive training, enhancing both the efficacy and safety of military personnel in complex, real-world environments.